2022
DOI: 10.1126/science.abj6647
|View full text |Cite
|
Sign up to set email alerts
|

LLPS of FXR1 drives spermiogenesis by activating translation of stored mRNAs

Abstract: Postmeiotic spermatids use a unique strategy to coordinate gene expression with morphological transformation, in which transcription and translation take place at separate developmental stages, but how mRNAs stored as translationally inert messenger ribonucleoproteins in developing spermatids become activated remains largely unknown. Here, we report that the RNA binding protein FXR1, a member of the fragile X–related (FXR) family, is highly expressed in late spermatids and undergoes liquid-liquid phase separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 63 publications
1
63
0
Order By: Relevance
“…7b ) which were reported to facilitate translation initiation during spermatogenesis 63 , 64 . A recent study showed that FXR1 also promotes translation together with EIF4G3 and PABPC1 to drive spermiogenesis 65 . EIF4G3 has also been shown to be required for male fertility, and its deficiency causes failed entry to the meiotic metaphase during spermatogenesis, defects also observed in PRRC2A-null spermatocytes 64 .…”
Section: Resultsmentioning
confidence: 99%
“…7b ) which were reported to facilitate translation initiation during spermatogenesis 63 , 64 . A recent study showed that FXR1 also promotes translation together with EIF4G3 and PABPC1 to drive spermiogenesis 65 . EIF4G3 has also been shown to be required for male fertility, and its deficiency causes failed entry to the meiotic metaphase during spermatogenesis, defects also observed in PRRC2A-null spermatocytes 64 .…”
Section: Resultsmentioning
confidence: 99%
“…To reach conditions that can most accurately capture the dynamics of translation, diverse UAS promoters together with a variety of available Gal4 drivers should be tested depending on the tissue of interest and the expression level of the tagged gene. Studies on mRNA localization and local translation have speculated that different mRNAs species may be translationally co-regulated [56][57][58] . To obtain independent translational readouts of different mRNA simultaneously, one can combine orthogonal tagging systems.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, it was recently discovered that liquid-liquid phase separation of RBPs can also promote translation of bound mRNAs. The RBP Fragile X Mental Retardation Syndrome-Related Protein 1 (FXR1) was shown to actively recruit and promote translation of its target mRNAs after undergoing LLPS ( Kang et al, 2022 ). It is conceivable that DDX3X may possess a similar function.…”
Section: Translation Regulation By Ddx3x and Its Physiological Conseq...mentioning
confidence: 99%